The men have the floor! An analysis of women's and men's participation in the Folketing's legislative debates - Midjord, Malthe Røpke; Bækgaard, Martin (Politica, 2025)
Although MPs have clear incentives to participate actively in legislative debates in the Danish parliament, the Folketing, female MPs participate significantly less than their male colleagues. This difference contributes to an already unequal parliamentary gender representation. Despite a rich research literature on parliamentary gender representation, we know little about why female MPs speak less than their male counterparts. Based on data from all legislative proceedings in the Folketing in 2009-2022, we find that the gender difference in participating actively in legislative debates is reduced by 32 percent when we control for MP roles as party spokespersons. Male MPs are more often spokespersons in policy areas with high legislative activity compared to women, which is why they more often have occasion to speak in the chamber.